The worksite heart health improvement project's impact on behavioral risk factors for cardiovascular disease in long-term care: A randomized control trial. (October 2018) - Doran, Kelly; Resnick, Barbara; Alghzawi, Hamzah; Zhu, Shijun
Abstract: Background: Long-term care workers are at high risk for cardiovascular disease, in part because of their poor health habits. Objective: The purpose of this study is to test the impact of the Worksite Heart Health Improvement Project (WHHIP) on subjective behavioral cardiovascular risk factors over time among long-term care staff. Design: The WHHIP was a 12-month cluster randomized control trial conducted in four long-term care facilities. The exercise, nutrition, and stress management intervention lasted 9-months and was implemented during paid work time. Setting and participants: Ninety-eight long-term care workers consented to participate in the study. Methods: Survey data included: mood, dietary salt intake, dietary fat intake, sleep quality, and sleep duration. Results: A significant positive short-term intervention effect at 9-month ( p  = .037) and long-term effect at 12-month for mood ( p  = .039) was found, signifying reduction in mood symptoms in the treatment group over time. The intervention group also showed longer sleep time ( p  = .016) and better sleep quality ( p  = .046) at 12-months. The intervention group had less dietary sodium intake at 9-months ( p  = .036); yet, this was not maintained over time. Conclusion: The WHHIP demonstrated the ability to improve participants' mood, sleep and sodium intake over time. Lessons learned particularly the challenges faced implementing the WHHIP and the solutions recommended provide critical insights to strengthen future programs with this population.